Towards a declarative modeling approach built on top of a CAD modeler. Issue 6 (1st November 2016) - Decriteau, Dorian; Pernot, Jean-Philippe; Daniel, Marc
ABSTRACT: Today's CAD modelers are very efficient in processing 3D shapes of CAD models by means of B-Rep modeling operators such as pad, pocket, shaft, groove, hole, fillet and so on. At a lower description level, those modeling operators are based on Euler operators acting directly on the faces, edges and vertices of the B-Rep models. Using such a top-down approach, the designers do not have to work on low-level geometric entities, but rather manipulate so-called structural and detail features to shape directly the CAD models. However, there is still a gap between the shapes the designers have in mind and the way they have to decompose them in a succession of modeling steps. This paper proposes a new declarative modeling approach to design industrial shapes allowing the designers to interact with a CAD software at a more conceptual level. The designers enter a high-level description of the expected shapes that is then transformed through scripts into traditional CAD operators successively called to create the shapes. Compared to the traditional feature-based approaches, our declarative modeling approach is closer to the way designers think. It saves time while keeping all the advantages of existing efficient CAD modelers. This new approach aims at quickly creating drafts rather than final shapes. Those drafts can then be modified using classical CAD software in which our new approach is fully embedded. This approach is a first step towards a declarative CAD modeler. GRAPHICAL ABSTRACT: